THE IMPLEMENTATION OF VIDEO BASED DIRECT DRIVE STARTER SIMULATOR TO IMPROVE MOTIVATION AND UNDERSTANDING OF AUTOMOTIVE STUDENTS - Febriyani, Githa Fitri; Permana, Tatang; Mubarak, Ibnu; Muhamad Noor, Ridwan adam; Sutia, Iyep; Widyaningsih, Indri (Universitas Pendidikan Indonesia, 2020)
his study aims to determine the motivation and learning outcomes of students by applying a video-based simulator to the direct drive type starter systemmaterial. This research is motivated by a lack of students’ understandingabout the starter system material in the electrical engine coursedue to the absence of the supporting learning media. This causes students to be less participate during the learning process whichis still focused on the lecturer (teacher-centered) because the teaching and learning activities tend to be monotonous and boring.This study used a pre-experimental method using one group pretest-posttest design research. The population in this study were students of S1 DPTM FPTK UPI batch2018 with a total of 97 students. The sample in this study were 39 students of automotive concentration class 2018. The results of this study showed the improvement of students’ motivationafter learning by usinga video-based starter systemsimulator which then obtain 44% value ofmotivation questionnaire. The result of students’ motivationis at the